Is robot-assisted laparoscopic myomectomy superior to laparoscopic myomectomy? - Faruk Abike; Ali Gemici; Fulya Gokalp Yavuz; Bashar Sammour; Ömer Lütfi Tapısız; İlkkan Dünder (Clinical and Experimental Obstetrics & Gynecology)
Background: To determine whether RLM (Robot-assisted Laparoscopic Myomectomy) or LM (Laparoscopic Myomectomy) provides better surgical and post-operative outcomes for patients willing to have minimally invasive myomectomy. Methods: In this retrospective cohort (Class II-2) analysis, all patients who underwent RLM and LM by a single expertise surgical team from January 1st, 2018 to March 31st, 2020 were identified. The patients’ characteristics, operative data, and post-operative outcomes were collected and statistically analyzed. Results: A total of 118 patients with an indication of myomectomy were included, 39 of whom underwent RLM, while 79 underwent LM. There were no significant differences among the groups in demographic characteristics (p > 0.05). RLM was associated with lower estimated blood loss (55.00 ± 39.11 mL vs. 110.80 ± 74.72 mL, respectively, p < 0.001) and larger myoma size (6.92 ± 1.88 cm vs. 6.00 ± 2.07 cm, p < 0.001) compared with LM. No significant differences were noted between the groups for other parameters (p > 0.05). Conclusions: Although RLM was associated with significantly less blood loss, this difference did not entail clinical implications. In general, both methods demonstrated similar clinical outcomes. For cost effectiveness, LM appears to outperform RLM, particularly in experienced hands.